Interventions designed to reduce sedentary behaviours in young people: a review of reviews. Issue 3 (17th December 2013) - Biddle, Stuart J H; Petrolini, Irene; Pearson, Natalie
Abstract : Background: Leisure time is increasingly spent in sedentary pursuits such as screen-viewing (eg, television/DVD viewing and computer use), motorised travel, school/work and sitting-based socialising (eg, social media and chatting). Sedentary screen time, particularly TV, appears to play an important role in the aetiology of obesity due to its co-occurrence with other unhealthy behaviours such as snacking on energy-dense foods, low levels of physical activity and inadequate sleep. More information is needed on how to reduce sedentary behaviours. Most interventions have focused on young people and a number of systematic reviews exist on this topic. Objective: To synthesise systematic reviews and meta-analyses of interventions aimed at decreasing sedentary behaviours among children and adolescents. Methods: Papers were located from computerised and manual searches. Included articles were English language systematic reviews or meta-analyses of interventions aiming at reducing sedentary behaviour in children (<11 years) and adolescents (12–18 years). Results: Ten papers met the inclusion criteria and were analysed. All reviews concluded some level of effectiveness in reducing time spent in sedentary behaviour. When an effect size was reported, there was a small but significant reduction in sedentary time (highest effect size=−0.29; CI −0.35 to −0.22). Moderator analyses showed a trend favouring interventions with children younger than 6 years. Effective strategies include the involvement of family, behavioural interventions and electronic TV monitoring devices. Conclusions: Results from systematic reviews and meta-analyses show that interventions to reduce children's sedentary behaviour have a small but significant effect. Future research should expand these findings examining interventions targeting different types of sedentary behaviours and the effectiveness of specific behaviour change techniques across different contexts and settings.